Hak Waris Laki-Laki Perkawinan Nyeburin dalam Hukum Adat Bali di Desa Adat Sawan Kabupaten Gianyar - Ni Kadek Ratna Dewi; I Made Suwitra; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
The kinship system that adheres to the Patrilineal system or better known to adhere to the male lineage system or in Balinese terms is commonly known as following the purus. Purusa will later become an heir and will inherit all the rights and obligations of his parents towards God. A Nyeburin marriage is the opposite if the wife has the status and position as purusa and the man has the status and position as pradana. This study aims to analyze the model of inheritance for boys who marry in Sawan Village, Gianyar Regency and explain the ownership rights to inheritance given by men in nyeburin marriages in Sawan Traditional Village, Gianyar Regency. The method used was empirical legal research, with a statutory and conceptual approach. Sources of data used were primary and secondary legal data. The results showed that the model of giving inheritance for boys who married in Sawan Village, Gianyar Regency was given a kind of gift in the form of dry land which was given to men who were willing to be son-in-law and to marry in order to give the property when the man -the man who agrees and agrees to do the marriage intercourse, then the land becomes the man's full right.